Plant Carbohydrate Binding Module Enhances Activity of Hybrid Microbial Cellulase Enzyme - Byrt, Caitlin S.; Cahyanegara, Ricky; Grof, Christopher P. (Frontiers in Plant Science, 2012)
A synthetic, highly active cellulase enzyme suitable for in planta production may be a valuable tool for biotechnological approaches to develop transgenic biofuel crops with improved digestibility. Here, we demonstrate that the addition of a plant derived carbohydrate binding module (CBM) to a synthetic glycosyl hydrolase (GH) improved the activity of the hydrolase in releasing sugar from plant biomass. A CEL-HYB1-CBM enzyme was generated by fusing a hybrid microbial cellulase, CEL-HYB1, with the carbohydrate-binding module (CBM) of the tomato (Solanum lycopersicum) SlCel9C1 cellulase. CEL-HYB1 and CEL-HYB1-CBM enzymes were produced in vitro using Pichia pastoris and the activity of these enzymes was tested using CMC, MUC and native crystalline cellulose assays. The presence of the CBM substantially improved the endo-glucanase activity of CEL-HYB1, especially against the native crystalline cellulose encountered in Sorghum plant cell walls. These results indicate that addition of an endogenous plant derived CBM to cellulase enzymes may enhance hydrolytic activity.